Anxiety and Depression Following Traumatic Brain Injury - Khoiriyah Khoiriyah; Nury Sukraeny; Sri Harmini; Nittiya Noysipoom; Suttatip Tumme; Aric Vranada; Satriya Pranata (Gonabad University of Medical Sciences, 2024)
There have been many studies on the occurrence of anxiety and depression following traumatic brain injury (TBI). However, these studies have primarily been conducted in developed countries with unrestricted access to resources and care environments. It is unclear whether patients with TBI in Southeast Asian countries, like Indonesia experience anxiety and depression to the same extent, given the differences in care provision post-discharge. This study aimed to examine the occurrence of anxiety and depression following TBI and their correlation with demographic factors such as age and gender, as well as health-related data including time since injury, severity of injury, functioning and disability, and social support. TBI patients were selected from medical records of individuals who had been discharged from the neurosurgery unit at least one month earlier and were capable of participating in a follow-up study. The hospital anxiety and depression scale (HADS) was utilized to assess anxiety and depression levels. In this study, a total of 100 patients were recruited, comprising 60% with mild TBI and 40% with moderate TBI. The findings revealed that 23% of the subjects experienced anxiety and 22% experienced depression. Social support, functioning and disability, age, and time since injury were statistically correlated with anxiety and depression (P<0.01). These results underscore the importance of promptly identifying and implementing interventions to alleviate or prevent these conditions. Such actions will ultimately improve the recovery process and overall well-being of TBI survivors.